The Power of Similars: Homoeopathy’s Dynamic Solution to Obsessive Compulsive Disorder (Homoeopathy for All, 2024)
Obsessive-compulsive disorder  (OCD) is a relatively rare neurosis  marked by persistent obsessions  and compulsions, impacting  approximately 2.5% of the  population. Its prevalence stands  at about 2.5% among the general  population and less than 5% among  psychiatric patients. Onset typically  occurs in adolescence, often before  the age of 30, and affects both  genders equally. Individuals with  above-average intelligence are  most commonly affected.
Keywords: OCD; Obsessive Compulsive Disorder; Homoeopa thy